Youtube Vidioes Utilization in Extensive Listening Using Metacognitive Strategy: A Narrative Study. - Refi Ranto Rozak (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2014)
Teaching extensive listening for pre-service English language teachers program is aimed at allowing them to receive a lot of comprehensible and enjoyablelistening input. Unfortunately, their lack of listening competence and unsupportable classroom situation are frequently the main barriers for their comprehension. It has been proven that the use of visual media in video can improve students‟ multiple cognitive connections and make learning easier by addressing their auditory or visual strength. Meanwhile, teacher-centered learning style and passive activities in listening influence uninteresting classroom atmosphere. Therefore, teachers need to apply effective strategies that involve their listening stages development. Metacognitive strategy is considered as the effective listening strategy that benefit the subjects through raising their awareness of the use of strategy and providing a kind of scaffolding as the subjectsgo through listening tasks in pre-, while-, and post-listening stages. The purpose of the present research article is to know the contribution of Youtube videos and metacognitive strategy to students‟ extensive listening comprehension. In addition, this article is to know the implication of Yotube videos and metacognitive strategy toward classroom situation. Data was collected through 6 groups (12 students) using narratives inquiry approach written which was obtained from listening logs. The data was obtained from observation in language laboratory as well. The findings show that Youtube videos and metacognitive strategy can improve students‟ extensive listening comprehension. It is hoped that in achieving the objectives in teaching and learning listening, it is necessary to select appropriate media and strategy.